2023
DOI: 10.1021/acsomega.3c02349
|View full text |Cite
|
Sign up to set email alerts
|

Application of aza-BODIPY as a Nitroaromatic Sensor

Bleda Can Sadikogullari,
Ilayda Koramaz,
Berkay Sütay
et al.

Abstract: Nitroaromatic explosive detection with high sensitivity and selectivity is requisite for civilian and military safety and the ecosystem. In this study, aza boron dipyrromethene (aza-BODIPY) dye was selected as a fluorescent-based chemosensor against nitroaromatic compounds (NACs) including 2,4,6-trinitrophenol (picric acid, TNP), 2,4,6-trinitrotoluene (TNT), and 2,4-dinitrotoluene (DNT). This dye molecule exhibits sharp fluorescent behavior with high quantum yields beyond the near-infrared region (NIR) and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…It is observed that the emission spectrum of BIBTB is significantly changed (Figure A) in the presence of picric acid (PA) with a notable red shift of the emission band (Δλ Em ∼ 37 nm) and a concurrent reduction of emission intensity. This indicates that BIBTB functions as a highly specific sensor for the identification of PA since it only exhibits striking changes in emission peak position when PA is present. …”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…It is observed that the emission spectrum of BIBTB is significantly changed (Figure A) in the presence of picric acid (PA) with a notable red shift of the emission band (Δλ Em ∼ 37 nm) and a concurrent reduction of emission intensity. This indicates that BIBTB functions as a highly specific sensor for the identification of PA since it only exhibits striking changes in emission peak position when PA is present. …”
Section: Resultsmentioning
confidence: 97%
“…For investigating the mechanism of PA detection, we have presented the relative energies of the frontier molecular orbitals of both BIBTB and PA, which demonstrate a favorable energy level alignment for the electron transfer from the photoexcited BIBTB to PA. , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations